(3QSGdI aj GdUHGZI GdcjejGhjIs - (3GHf hMTjI , CMeO Hf Ydj Hf bjS Hf GdeNJGQ Hf YHO GdcQje Hf MQKjG, CHh HcQ,J (B291 (3g` s
(3ChdgG (B:s
(3bGd CHh HcQ GdeYQha HGHf hMTi , ai QSGdI cJHgG dGHfg HYO cdGe Whjd (B: (3aChd eG CYdec jG Hfi ef Pdc s
(3BNQgG (B:s
(3jJHjf ddfGXQ YfO EdbGA GdMLQ gd gh ef MLQ Mb Ch ef HYV YbGbjQ GdfHGJ Ch GdeYOf aYGde Pdc GfJgi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B9 - (3U(B10s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B170 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B23s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B55 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs